The Impact of Transportation Traffic Noise on Merauke City Road Crossing - Algiranto Algiranto; Anderias Henukh; Rikardus Feribertus Nikat; Martha Loupatty (JIPF (Jurnal Ilmu Pendidikan Fisika), 2022)
Noise caused by transportation significantly exceeds the 55 dBA. The purpose of this study was to determine the level of transportation traffic noise at the Merauke city crossing and its solutions. Noise caused The lack of proper attention to the impact of noise from traffic flow at a crossroads. The Development of additional techniques for noise reduction in this area is needed. The results obtained are very important for areas with solutions at every highway intersection The results obtained are very important knowing the noise above the standard value at every highway intersection. This research develops techniques to reduce transportation traffic noise at the crossroads of Merauke city which are applied in design practice. Experimental studies in real conditions in the characteristic areas of Merauke City using sound level meter measurements. This research was carried out experimentally by taking measurements at each crossroads and theoretical solving methods. The good convergence results confirm the impact of noise on the immediate area with a slightly higher crossing than the value on a normal two-lane road. The proposed solution will allow providing additional protection against transportation noise.